Contribution to the knowledge of the Sardinian aphid fauna (Hemiptera Aphididae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A survey of Sardinian aphid fauna is given in this paper, either based on previous literary records or newly acquired data. The latter come from identifying about 300 aphid samples collected over 1986-2007. The results reveal 98 new aphid species, three of which (Chaitophorus gomesi, C. similis and Acyrthosiphon malvae ssp. sanguisorbae) are for the first time reported here as a contribution to Italian aphid fauna. For each newly recorded Sardinian aphid species and/or subspecies, the data lists their host plants and sampling localities, adding supplementary taxonomic and biological information for a few of them. So far, Sardinian aphid fauna have 285 species-taxa and - despite being easily implemented by further contributions - put that isle among the better faunistically investigated regional territories in Italy.
Keywords: aphid fauna; taxonomy; Sardinia region; Italy